# 10.3E: Basic Theory of Homogeneous Linear Systems (Exercises)

## Q10.3.1

1. Prove: If ({f y}_1), ({f y}_2), …, ({f y}_n) are solutions of ({f y}'=A(t){f y}) on ((a,b)), then any linear combination of ({f y}_1), ({f y}_2), …, ({f y}_n) is also a solution of ({f y}'=A(t){f y}) on ((a,b)).

2. In Section 5.1 the Wronskian of two solutions (y_1) and (y_2) of the scalar second order equation

[P_0(x)y''+P_1(x)y'+P_2(x)y=0 ag{A}]

was defined to be

[W=left|egin{array}{cc} y_1&y_2 y'_1&y'_2end{array} ight|. onumber ]

1. Rewrite (A) as a system of first order equations and show that (W) is the Wronskian (as defined in this section) of two solutions of this system.
2. Apply Equation 10.3.6 to the system derived in (a), and show that [W(x)=W(x_0)expleft{-int^x_{x_0}{P_1(s)over P_0(s)}, ds ight}, onumber ] which is the form of Abel’s formula given in Theorem 9.1.3.

3. In Section 9.1 the Wronskian of (n) solutions (y_1), (y_2), …, (y_n) of the (n-)th order equation

[P_0(x)y^{(n)}+P_1(x)y^{(n-1)}+cdots+P_n(x)y=0 ag{A}]

was defined to be

[W=left|egin{array}{cccc} y_1&y_2&cdots&y_n y'_1&y'_2&cdots&y_n' vdots&vdots&ddots&vdots y_1^{(n-1)}&y_2^{(n-1)}&cdots&y_n^{(n-1)} end{array} ight|. onumber ]

1. Rewrite (A) as a system of first order equations and show that (W) is the Wronskian (as defined in this section) of (n) solutions of this system.
2. Apply Equation 10.3.6 to the system derived in (a), and show that [W(x)=W(x_0)expleft{-int^x_{x_0}{P_1(s)over P_0(s)}, ds ight}, onumber ] which is the form of Abel’s formula given in Theorem 9.1.3.

4. Suppose

are solutions of the (2 imes 2) system ({f y}'=A{f y}) on ((a,b)), and let

thus, (W) is the Wronskian of ({{f y}_1,{f y}_2}).

1. Deduce from the definition of determinant that [W'=left|egin{array}{cc} {y'_{11}}&{y'_{12}} {y_{21}}& {y_{22}}end{array} ight| +left|egin{array}{cc} {y_{11}}&{y_{12}} {y'_{21}}&{y'_{22}}end{array} ight|. onumber ]
3. Use properties of determinants to deduce from (a) and (a) that [left|egin{array}{cc} {y'_{11}}&{y'_{12}} {y_{21}}& {y_{22}}end{array} ight|=a_{11}Wquad ext{and} quad left|egin{array}{cc} {y_{11}}&{y_{12}} {y'_{21}}&{y'_{22}}end{array} ight|=a_{22}W. onumber ]
4. Conclude from (c) that [W'=(a_{11}+a_{22})W, onumber ] and use this to show that if (a

5. Suppose the (n imes n) matrix (A=A(t)) is continuous on ((a,b)). Let

[Y= left[egin{array}{cccc} y_{11}&y_{12}&cdots&y_{1n} y_{21}&y_{22}&cdots&y_{2n} vdots&vdots&ddots&vdots y_{n1}&y_{n2}&cdots&y_{nn} end{array} ight], onumber ]

where the columns of (Y) are solutions of ({f y}'=A(t){f y}). Let

[r_i=[y_{i1}, y_{i2}, dots, y_{in}] onumber ]

be the (i)th row of (Y), and let (W) be the determinant of (Y).

1. Deduce from the definition of determinant that [W'=W_1+W_2+cdots+W_n, onumber ] where, for (1 le m le n), the (i)th row of (W_m) is (r_i) if (i e m), and (r'_m) if (i=m).
2. Use the equation (Y'=A Y) and the definition of matrix multiplication to show that [r'_m=a_{m1}r_1+a_{m2} r_2+cdots+a_{mn}r_n. onumber ]
3. Use properties of determinants to deduce from (b) that [det (W_m)=a_{mm}W. onumber ]
4. Conclude from (a) and (c) that [W'=(a_{11}+a_{22}+cdots+a_{nn})W, onumber ] and use this to show that if (a

6. Suppose the (n imes n) matrix (A) is continuous on ((a,b)) and (t_0) is a point in ((a,b)). Let (Y) be a fundamental matrix for ({f y}'=A(t){f y}) on ((a,b)).

1. Show that (Y(t_0)) is invertible.
2. Show that if ({f k}) is an arbitrary (n)-vector then the solution of the initial value problem [{f y}'=A(t){f y},quad {f y}(t_0)={f k} onumber ] is [{f y}=Y(t)Y^{-1}(t_0){f k}. onumber ]

7. Let

[A=left[egin{array}{cc}{2}&{4}{4}&{2}end{array} ight], quad {f y}_1=left[egin{array}{c} e^{6t} e^{6t} end{array} ight], quad {f y}_2=left[egin{array}{r} e^{-2t} -e^{-2t}end{array} ight], quad {f k}=left[egin{array}{r}-3 9end{array} ight]. onumber ]

1. Verify that ({{f y}_1,{f y}_2}) is a fundamental set of solutions for ({f y}'=A{f y}).
2. Solve the initial value problem [{f y}'=A{f y},quad {f y}(0)={f k}. ag{A}]
3. Use the result of Exercise 10.3.6 (b) to find a formula for the solution of (A) for an arbitrary initial vector ({f k}).

8. Repeat Exercise 10.3.7 with

[A=left[egin{array}{cc}{-2}&{-2}{-5}&{1}end{array} ight], quad {f y}_1=left[egin{array}{r} e^{-4t} e^{-4t}end{array} ight], quad {f y}_2=left[ egin{array}{r}-2e^{3t} 5e^{3t}end{array} ight], quad {f k}=left[egin{array}{r} 10 -4end{array} ight]. onumber ]

9. Repeat Exercise 10.3.7 with

[A=left[egin{array}{cc}{-4}&{-10}{3}&{7}end{array} ight], quad {f y}_1=left[egin{array}{r}-5e^{2t} 3e^{2t} end{array} ight], quad {f y}_2=left[egin{array}{r} 2e^t -e^t end{array} ight], quad {f k}=left[egin{array}{r}-19 11end{array} ight ]. onumber ]

10. Repeat Exercise 10.3.7 with

[A=left[egin{array}{cc}{2}&{1}{1}&{2}end{array} ight], quad {f y}_1=left[egin{array}{r} e^{3t} e^{3t} end{array} ight], quad {f y}_2=left[egin{array}{r}e^t -e^tend{array} ight], quad {f k}=left[egin{array}{r} 2 8 end{array} ight]. onumber ]

11. Let

[egin{aligned} A&= left[egin{array}{ccc}{3}&{-1}&{-1}{-2}&{3}&{2}{4}&{-1}&{-2}end{array} ight] , {f y}_1&=left[egin{array}{c} e^{2t} 0 e^{2t}end{array} ight], quad {f y}_2=left[egin{array}{c} e^{3t} -e^{3t} e^{3t}end{array} ight], quad {f y}_3=left[egin{array}{c} e^{-t} -3e^{-t} 7e^{-t} end{array} ight], quad {f k}=left[egin{array}{r} 2 -7 20end{array} ight].end{aligned} onumber ]

1. Verify that ({{f y}_1,{f y}_2,{f y}_3}) is a fundamental set of solutions for ({f y}'=A{f y}).
2. Solve the initial value problem [{f y}'=A{f y}, quad {f y}(0)={f k}. ag{A}]
3. Use the result of Exercise 10.3.6 (b) to find a formula for the solution of (A) for an arbitrary initial vector ({f k}).

12. Repeat Exercise 10.3.11 with

[egin{aligned} A&=left[egin{array}{ccc}{0}&{2}&{2}{2}&{0}&{2}{2}&{2}&{0}end{array} ight], {f y}_1&=left[egin{array}{c}-e^{-2t} 0 e^{-2t} end{array} ight], quad {f y}_2=left[egin{array}{c}-e^{-2t} e^{-2t} 0end{array} ight], quad {f y}_3=left[egin{array}{c} e^{4t} e^{4t} e^{4t}end{array} ight], quad {f k}=left[egin{array}{r} 0 -9 12end{array} ight].end{aligned} onumber ]

13. Repeat Exercise 10.3.11 with

[egin{aligned} A&=left[egin{array}{ccc}{-1}&{2}&{3}{0}&{1}&{6}{0}&{0}&{-2}end{array} ight], {f y}_1&=left[egin{array}{c} e^t e^t 0end{array} ight], quad {f y}_2=left[egin{array}{c} e^{-t} 0 0end{array} ight], quad {f y}_3=left[egin{array}{c} e^{-2t} -2e^{-2t} e^{-2t}end{array} ight], quad {f k}=left[egin{array}{r} 5 5 -1 end{array} ight].end{aligned} onumber ]

14. Suppose (Y) and (Z) are fundamental matrices for the (n imes n) system ({f y}'=A(t){f y}). Then some of the four matrices (YZ^{-1}), (Y^{-1}Z), (Z^{-1}Y), (Z Y^{-1}) are necessarily constant. Identify them and prove that they are constant.

15. Suppose the columns of an (n imes n) matrix (Y) are solutions of the (n imes n) system ({f y}'=A{f y}) and (C) is an (n imes n) constant matrix.

1. Show that the matrix (Z=YC) satisfies the differential equation (Z'=AZ).
2. Show that (Z) is a fundamental matrix for ({f y}'=A(t){f y}) if and only if (C) is invertible and (Y) is a fundamental matrix for ({f y}'=A(t){f y}).

16. Suppose the (n imes n) matrix (A=A(t)) is continuous on ((a,b)) and (t_0) is in ((a,b)). For (i=1), (2), …, (n), let ({f y}_i) be the solution of the initial value problem ({f y}_i'=A(t){f y}_i,; {f y}_i(t_0)={f e}_i), where

[{f e}_1=left[egin{array}{c} 1 vdotsend{array} ight],quad {f e}_2=left[egin{array}{c} 01 vdotsend{array} ight],quadcdotsquad {f e}_n=left[egin{array}{c} 0 vdots1end{array} ight]; onumber ]

that is, the (j)th component of ({f e}_i) is (1) if (j=i), or (0) if (j e i).

1. Show that({{f y}_1,{f y}_2,dots,{f y}_n}) is a fundamental set of solutions of ({f y}'=A(t){f y}) on ((a,b)).
2. Conclude from (a) and Exercise 10.3.15 that ({f y}'= A(t){f y}) has infinitely many fundamental sets of solutions on ((a,b)).

17. Show that (Y) is a fundamental matrix for the system ({f y}'=A(t){f y}) if and only if (Y^{-1}) is a fundamental matrix for ({f y}'=- A^T(t){f y}), where (A^T) denotes the transpose of (A). HINT: See Exercise 10.3.11.

18. Let (Z) be the fundamental matrix for the constant coefficient system ({f y}'=A{f y}) such that (Z(0)=I).

1. Show that (Z(t)Z(s)=Z(t+s)) for all (s) and (t). HINT: For fixed (s) let (Gamma _{1}(t)=Z(t)Z(s)) and (Gamma _{2}(t)=Z(t+s)). Show that (Gamma _{1}) and (Gamma_{2}) are both solutions of the matrix initial value problem (Gamma '=AGamma , :Gamma (0)=Z(s)). Then conclude from Theorem 10.2.1 that (Gamma _{1}=Gamma _{2}).
2. Show that ((Z(t))^{-1}=Z(-t)).
3. The matrix (Z) defined above is sometimes denoted by (e^{tA}). Discuss the motivation for this notation.